Prevalence of Shoulder Pain among Female Students Carrying Heavy Bag - A Gul Memon, M. Khan Soomro, Mehjabeen Farooqui, Jaimala Rathi, M. Sanaullah, S. Shah, M. I. Hussain, Maryam, F. Chaudhary (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the prevalence of shoulder pain carrying heavy bags in female students Methodology: This was across-sectional study and data were collected through a convenient sampling technique. Data collected from theuniversity female students of sind. A visual analog scale was used to assess the intensity of pain, and To assess the burden of shoulder pain, data were collected using a self-administered questionnaire. Data was analyzed through SPSS Version 22. Results: Results indicate thatthe meanage±SDof participants were 22.8±1.99, mean height±SD were 61.10±3.7 in inches, mean weight±SD were 54.9±3.4kg. The result of this study shows that majority of students are experiencing shoulder pain by carrying uncomfortable bags in routine life. About 38.3% of messenger bags are comfortable to carry. The majority (67.5%) of the students have shoulder pain during activity, 34.2% at its worth and minority of the students are suffering from sleep disturbance due to shoulder pain. Practical implication: few studies have assessed the relationship between university students and heavy bags. Therefore, our hypothesis is that the use of overweight shoulder bags can influence the occurrence of shoulder pain. Thus, the present study aimed to determine the prevalence of shoulder pain carrying heavy bags in female students Conclusion: It is concluded that there is high prevalence of shoulder pain due to tote type of bags among university going females. The shoulder bags cause moderate to severe shoulder pain and mostly dull aching and generalized type of pain cause by shoulder bags. Keywords: Females students, Heavy bags, Prevalence, Shoulder pain